True Incidence of Gleason 6 Pathology in Patients with Metastatic Castration Resistant Prostate Cancer (mCRPC). Issue 1 (January 2017) - Böker, Alena; Kuczyk, Markus; Kramer, Mario; Merseburger, Axel; Krüger, Katharina; Imkamp, Florian; Klot, Christoph
Abstract Introduction Recent evidence from histology studies regarding random prostate biopsies hint toward a relationship between higher biopsy Gleason score and the development of metastatic castration resistant prostate cancer (mCRPC). However, prostate biopsy underestimates final pathology in about one-third of patients. We evaluated the final whole gland pathology from radical prostatectomy exclusively in order to assess the true risk of progressing to the mCRPC state for patients with confirmed Gleason ≤6 prostate cancer. Methods Patients with confirmed mCRPC from our outpatient clinic were retrospectively evaluated with regard to whole gland pathology and the occurrence of Gleason 6 histology from 1995 to 2015. Conversely, patients with confirmed Gleason 6 pathology from our institutional database were followed up for the development of mCRPC from 2001 to 2015. Kaplan–Meier analysis and the log rank test were applied for survival analysis. The binomial test was used to evaluate occurrence rates of Gleason ≤6 pathologies in mCRPC patients. Results Out of 62 patients with mCRPC none had confirmed Gleason 6 pathology on whole gland histology of the prostate. Out of 86 patients with confirmed Gleason 6 pathology none developed an mCRPC over the follow-up period. Conclusion The development of mCRPC in patients with true Gleason 6 pathology is very rare and could not be confirmed in our series. This finding may have important implications in future treatment planning.